Evaluation of genotoxic and cytotoxic effects of Glyphosate on Allium cepa - Fattah, Yousif M.; Omer, Ali H. (Technium BioChemMed, 2021)
Glyphosate is a broad-spectrum herbicide used mostly in crops. This study looked at the genotoxic and Glyphosate has a cytotoxic effect on Allium cepa. As toxicity markers, the Mitotic index, chromosomal aberrations, formations of Micronucleus, germination percentage, root duration, and seed weight were used. Allium cepa seeds were afflicted with distinct concentrations (0.5, 1.0, 2.0 and 4.0 ml/l) of Glyphosate for 24 h treatment periods. The results reveal that pesticide Glyphosateis capable to reduce root growth and causes chromosomal aberrations;consisting of an anaphase bridge, ring chromosome, binucleated cells, multipolarity, Fragment chromosome, vagrant chromosome, chromatid gaps, star anaphase. With increasing Glyphosate concentration, the mitotic index decreased rapidly. In conclusion, our findings indicate that used pesticidemay be toxic to living organism.